“Estudio de los métodos para el desarrollo de los procesos de purificación, concentración y separación de proteínas presentes en el lactosuero.” - Chipantiza Naula, Marco Roberto (2021)
At the OECD/FAOprojection, the world milk production is forecasting to increaseto 175million tonsby 2024.Thecheesewillcontinuebeing the mostimportant dairy product, itrepresented about 40%of elaborated milk around the world. This cheeseproduction brings with itself amayor production of dairy whey. Theproteins present in thesub product of dairy whey arenot constituted the mostmajorfraction, but itis the mostinteresting in the economicand nutritional lands. Thepresented researchwork has thepurposecarrying out to study ofmethods fordevelopmentpurifying,concentrationandseparating processes of proteins present in the dairywhey what makeeasy thediversification of production in the dairy industry. Themethodology forstudyisthe search of updated information about the types ofdairywheyexist, the composition’s analysis of each of them and the methods selection that makeeasily the proteins’ separating presentin the sub-product, theirpurifying andconcentration. With the knowledgeof thesemethods weperformed the proposal about the wholereuseof dairy whey in different industries. As conclusionof this work wehavebeen consideredthat membranetechnologiesarethemost efficientto separateand concentratethe dairy whey proteins and the electrophoresismethod to purify andseparate them.In theproposal of integral making advantageof the sub-product, the foodindustry is considered as the most representative in its reuse.